Exploring the role of language proficiency, gender, track specialization, and IELTS scores in Saudi EFL learners’ metacognitive reading strategies - Asma Alshehri; Ebtesam Abdulhaleem; Afzal Khan (Cogent Education)
This study examines how English language proficiency, track specialization, gender, and IELTS achievement levels contribute to metacognitive awareness of reading strategies among first-year university EFL learners. While previous studies have explored some of these variables individually, a comprehensive investigation that considers their interrelationships is lacking. Thus, this study aims to fill this research gap by examining the interplay between these factors among EFL learners. 464 students participated in the study and completed the Metacognitive Awareness of Reading Strategies Inventory (MARSI), developed and validated by Mokhtari and Reichard (2002). Data were analysed using SPSS version 22, utilizing descriptive and inferential statistical methods. Contrary to prior research, all EFL learners reported a medium level of metacognitive reading strategies (Mean= 3.40). These strategies significantly contribute to academic excellence and improved reading performance among proficient learners. Regardless of proficiency, EFL learners reported medium use of reading strategies. In the IELTS reading section, strategies correlate positively with scores. All tracks exhibit medium use of reading strategies, with students majoring in health using them more frequently, particularly support strategies. However, gender differences in reading strategy use are insignificant. The findings offer insights into enhancing academic outcomes by integrating metacognitive reading strategies in EFL curricula design.